Histomorphologisch definierte Nierenzellkarzinome 2025: Aktuelle WHO-Klassifikation und sich abzeichnende zukünftige Subtypen - Stöhr, Christine; Fiegl, August; Bercebal, C.; Agaimy, Abbas; Hartmann, Arndt (Die Pathologie, 2025)
BACKGROUND: The latest edition of the WHO classification of urinary and male genital tumours was published in 2022. The revision was based on the newest scientific literature. This article summarizes the updated recommendations regarding the classification of histomorphologically defined tumours. RESULTS AND CONCLUSIONS: The current edition of the WHO classification made some adjustments on the classification of histomorphologically defined tumour types. Papillary renal cell carcinoma is no longer categorized into two subtypes. Also, the new classification recognized the benign nature of clear cell papillary tumours, which are no longer regarded as carcinomas. Finally, several emerging renal tumours were introduced.
EVALuna2:585361